Pengaruh Social Media Marketing Terhadap Purchase Intention Di Teko Healthy Resto Medan - Jackie; Rina Friska B. Siahaan; Dewi Anggraini; Willi Chandra; Fauzi A.M. Hutabarat (Yayasan Literasi Sains Indonesia, 2022)
Teko Healthy Resto is a restaurant that provides menus and food dishes with 100% natural ingredients from plants (Vegan).The purpose of this study is: